Morphometric Analysis of the Lateral Atlantoaxial Joints in Patients with an Old Type II Odontoid Fracture and Atlantoaxial Dislocation: A Study Based on CT Analysis - Ma, Fei; Liao, Yehui; Tang, Qiang; Tang, Chao; Luo, Ning; He, Hongchun; Yang, Sheng; Wang, Qing; Zhong, Dejun (Spine (Philadelphia, Pa. 1976), 2021)
The morphological features of the lateral atlantoaxial joints (LAJs) in patients with old type II odontoid fractures and atlantoaxial dislocation have not been fully analyzed. Our study found the changes in morphological features of the LAJs in some patients, and revealed the causes and consequences of the changes in morphological features of the LAJs.